2000
DOI: 10.1108/14717794200000012
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate care for older people: Using action research to develop reflective nursing practice in a rehabilitation setting

Abstract: The importance of developing intermediate care options for older people is gaining increasing prominence in the UK with the promotion of new health and social care partnerships. Consequent changes in practice and values are demanded from staff. An action research approach provides a process of generating information linked to dialogues which facilitate such changes. This article draws on a case study of nursing staff working with older people in a newly‐defined rehabilitation setting in a Welsh community hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Lehmann et al (2004) argued that "collaborative inquiry is a powerful tool to develop reflective capacity among health workers", and Moffatt et al (2005) outlined a process for community practice research as a reflective process. Walker & Poland (2000) reported on an action research cycle that provided a process of generating information which facilitated positive and cost-effective changes to practice. The research reported in this paper was not instigated 'from above' and was developed and led by a health care assistant who had been taught research skills.…”
Section: Discussionmentioning
confidence: 99%
“…Lehmann et al (2004) argued that "collaborative inquiry is a powerful tool to develop reflective capacity among health workers", and Moffatt et al (2005) outlined a process for community practice research as a reflective process. Walker & Poland (2000) reported on an action research cycle that provided a process of generating information which facilitated positive and cost-effective changes to practice. The research reported in this paper was not instigated 'from above' and was developed and led by a health care assistant who had been taught research skills.…”
Section: Discussionmentioning
confidence: 99%
“…In group interviews, care staff in a rehabilitation unit of a Welsh community hospital admitted that they often found themselves 'doing for' patients because it was quicker than waiting for residents to dress themselves, for example. Staff said it was frustrating not having more time to spend with residents and having to rush through routine tasks in order to leave time for rehabilitation (Walker & Poland, 2000).…”
Section: Exercise and Activity -A Priority?mentioning
confidence: 99%